Determination of Mahkota Gold Pringsewu Customer Satisfaction - Wulandari, Adellia; Warganegara , Tri Lestira Putri (Politeknik Negeri Ambon, 2024)
Because of their abundance, Pringsewu's gold stores face fierce competition. Service quality, product quality, product design, and gold cleaning quality are what distinguish one business from the others and help it maintain customer loyalty. The goal of this study is to discover and explain how marketing messages and product quality influence customer satisfaction. This research takes a quantitative approach. There were 110 participants in this research overall. Using the Simple Random Sampling approach, 86 respondents were selected from the Mahkota Gold Pringsewu customer base for this study. This study relied on primary data. The data for this study was gathered using a Likert scale questionnaire technique. According to the findings of the study on Determining Customer Satisfaction at Mahkota Gold Pringsewu, there is a positive and significant relationship between product quality and customer satisfaction; there is also a positive and significant relationship between product quality and marketing communication, and there is a positive and significant relationship between the two for Mahkota Gold Pringsewu customers. This implies that high-quality products and marketing messages have a big influence on consumer happiness.